Land application of sewage sludge (biosolids) in Australia: risks to the environment and food crops - Pritchard, Deborah; Penney, N.; McLaughlin, M.; Rigby, Hannah; Schwarz, Karen (IWA Publishing, 2010)
Australia is a large exporter of agricultural products, with producers responsible for a range of quality assurance programs to ensure that food crops are free from various contaminants of detriment to human health. Large volumes of treated sewage sludge (biosolids), although low by world standards, are increasingly being recycled to land, primarily to replace plant nutrients and to improve soil properties; they are used in agriculture, forestry, and composted. The Australian National Biosolids Research Program (NBRP) has linked researchers to a collective goal to investigate nutrients and benchmark safe concentrations of metals nationally using a common methodology, with various other research programs conducted in a number of states specific to regional problems and priorities. The use of biosolids in Australia is strictly regulated by state guidelines, some of which are under review following recent research outcomes. Communication and research between the water industry, regulators and researchers specific to the regulation of biosolids is further enhanced by the Australian and New Zealand Biosolids Partnership (ANZBP).This paper summarises the major issues and constraints related to biosolids use in Australia using specific case examples from Western Australia, a member of the Australian NBRP, and highlights several research projects conducted over the last decade to ensure that biosolids are used beneficially and safely in the environment. Attention is given to research relating to plant nutrient uptake, particularly nitrogen and phosphorus (including that of reduced phosphorus uptake in alum sludge-amended soil); the risk of heavy metal uptake by plants, specifically cadmium, copper and zinc; the risk of pathogen contamination in soil and grain products; change to soil pH (particularly following lime-amended biosolids); and the monitoring of faecal contamination by biosolids in waterbodies using DNA techniques. Examples of products that are currently produced in Western Australia from sewage sludge include mesophilic anaerobically digested and dewatered biosolids cake, lime-amended biosolids, alum sludge and compost.